ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT SEWA SUKUK IJARAH STUDI KASUS PADA PERUSAHAAN YANG MENERBITKAN SUKUK IJARAH DI BURSA EFEK INDONESIA TAHUN 2015-2020 - Eka Nuraini Rachmawati; Saputra, Randi (Journal Of Islamic Finance And Accounting Research, 2022)
This study aims to determine whether Gross Domestic Product, Company Size, Bond Maturity, Debt to Equity Ratio (DER) affect the Sukuk Ijarah Rental Rate (Case Study on Companies Issuing Sukuk Ijarah In Indonesia Stock Exchange 2015-2020). The sample used in this study were 5 companies with the analytical method used, namely Quantitative Analysis. The results showed partially the variables Gross Domestic Product, Company Size, and Debt to Equity Ratio (DER) had no significant effect on the rental rate of Sukuk Ijarah and simultaneously Bond Maturity has a significant effect on the Rental Rate of Sukuk Ijarah.